2015
DOI: 10.1016/j.ehb.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Combat exposure and migraine headache: Evidence from exogenous deployment assignment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…In Table , we use data from the NLSAAH to descriptively explore the credibility of the exogeneity of deployment assignment, in a spirit similar to Cesur, Sabia, and Tekin (, ) and Cesur and Sabia (forthcoming). Consistent with those studies, we find that conditional on military rank, timing of service, branch, and occupation, deployment assignment is orthogonal to a wide set of background characteristics: age, race, height, weight, years of schooling attained, religious affiliation, maternal educational attainment, parental marital status when the respondent was an adolescent, parental income when the respondent was an adolescent, health insurance status, as well as the respondent's predeployment risky health behaviors (smoking, binge drinking, and drug use), measured analogously to the outcome variables, when the respondents were in high school , ,…”
Section: Empirical Approachmentioning
confidence: 53%
See 2 more Smart Citations
“…In Table , we use data from the NLSAAH to descriptively explore the credibility of the exogeneity of deployment assignment, in a spirit similar to Cesur, Sabia, and Tekin (, ) and Cesur and Sabia (forthcoming). Consistent with those studies, we find that conditional on military rank, timing of service, branch, and occupation, deployment assignment is orthogonal to a wide set of background characteristics: age, race, height, weight, years of schooling attained, religious affiliation, maternal educational attainment, parental marital status when the respondent was an adolescent, parental income when the respondent was an adolescent, health insurance status, as well as the respondent's predeployment risky health behaviors (smoking, binge drinking, and drug use), measured analogously to the outcome variables, when the respondents were in high school , ,…”
Section: Empirical Approachmentioning
confidence: 53%
“…The estimation sample includes 565 individuals aged 25–32 years at the third follow‐up survey (1) who had served as an active duty service member and been deployed overseas at least once by the time of Wave IV survey; (2) whose military service started after the Wave I interview; and (3) who provided nonmissing information on combat exposure and the outcomes under study . As discussed by Cesur, Sabia, and Tekin (, ) and Cesur and Sabia (forthcoming), a key advantage of the NLSAAH is that it contains information on observables available to Human Resources Command when making deployment assignments: service members' military branch, rank, occupation, and length of military service.…”
Section: Data and Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…We contribute to a growing body of literature that has examined the effects of combat deployments on a number of medium‐term and long‐term outcomes including violence, health, homelessness, family structure, and education (Ackerman, Porter, & Sullivan 2020; Armey & Lipow 2016; Cesur, Chesney, & Sabia 2016; Cesur & Sabia 2016; Cesur, Sabia, & Tekin 2013, 2015; Engel, Gallagher, & Lyle 2010; Lyle 2006; Negrusa, Negrusa, & Hosek 2014; Shen, Cunha, & Williams 2016). Consistent with the previous literature, we use the exogeneity of combat deployments to estimate the effect of combat deployments to Iraq or Afghanistan on casualty rates (see Lyle [2006] for elaboration).…”
Section: Introductionmentioning
confidence: 99%
“…9 A few small cohort studies have shown statistically signi cant relationships between migraine and external stress factors, in particular work-related stress 10,11 and stress from civil war, terrorism, and combat. [12][13][14] Why is migraine the number one chronic disease among those of working age in developed countries, where work-related stress is ubiquitous? And why is migraine the number one chronic disease in developing countries suffering from con ict or civic unrest or large refugee in ows, such as Afghanistan, Syria, Venezuela, Colombia, Jordan, Iraq, Lebanon and Palestine?…”
mentioning
confidence: 99%